Biomaterials in cardiac tissue engineering: Ten years of research survey - Chen, Qi-Zhi; Harding, Sian E.; Ali, Nadire N.; Lyon, Alexander R.; Boccaccini, Aldo R. (Materials Science & Engineering R-Reports, 2008)
Driven by enormous clinical need, myocardial tissue engineering has become a prime focus of research within the field of tissue engineering. Myocardial tissue engineering combines isolated functional cardiomyocytes and a biodegradable or nondegradable biomaterial to repair diseased heart muscle. The challenges in heart muscle engineering include cell related issues (such as scale up in a short timeframe, efficiency of cell seeding or cell survival rate, and immune rejection), the design and fabrication of myocardial tissue engineering substrates, and the engineering of tissue constructs in vitro and in vivo. Several approaches have been put forward, and a number of models combining various polymeric biomaterials, cell sources and bioreactors have been developed in the last 10 years for myocardial tissue engineering. This review provides a comprehensive update on the biomaterials, as well as cells and biomimetic systems, used in the engineering of the cardiac muscle. The article is organized as follows. A historic perspective of the evolution of cardiac medicine and emergence of cardiac tissue engineering is presented in the first section. Following a review on the cells used in myocardial tissue engineering (second section), the third section presents a review on biomaterials used in myocardial tissue engineering. This section starts with an overview of the development of tissue engineering substrates and goes on to discuss the selection of biomaterials and design of solid and porous substrates. Then the applications of a variety of biomaterials used in different approaches of myocardial tissue engineering are reviewed in great detail, and related issues and topics that remain challenges for the future progress of the field are identified at the end of each subsection. This is followed by a brief review on the development of bioreactors (fourth section), which is an important achievement in the field of myocardial tissue engineering, and which is also related to the biomaterials developed. At the end of this article, the major achievements and remaining challenges are summarized, and the most promising paradigm for the future of heart muscle tissue engineering is proposed (fifth section). © 2007 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.biomat
Keywords: Biomaterials; Bioreactors; Cardiac muscle; Cell therapy; Polymers; Tissue engineering